The OECD Water Governance Principles in Flood Risk Management: Understanding Conflicts and Frictions in Dutch Flood Protection. Issue 3 (1st December 2022) - Keller, Nadine; Tempels, Barbara; Hartmann, Thomas
Abstract: The OECD Water Governance Principles provide a guideline for good water governance. However, these principles can conflict with each other when applied in practice. This contribution aims to understand which dilemmas arise and how such conflicts play out. It is explored in an in-depth case study on Dutch flood risk management in which conflicts between the principles emerge when applied to flood risk management practice. Interviews with water managers were used to collect data on which principles contradict each other and how these conflicts work out in practice. The study reveals that although the principles seem obvious, some principles indeed clash when applying them, while others do not lead to conflicts. Principles on efficiency, trust, and engagement have high potential for conflicts.